Enhancing Understanding of the Hydrological Cycle via Pairing of Process‐Oriented and Isotope Ratio Tracers. (6th October 2021) - Fiorella, Richard P.; Siler, Nicholas; Nusbaumer, Jesse; Noone, David C.
Abstract: The hydrologic cycle couples the Earth's energy and carbon budgets through evaporation, moisture transport, and precipitation. Despite a wealth of observations and models, fundamental limitations remain in our capacity to deduce even the most basic properties of the hydrological cycle, including the spatial pattern of the residence time (RT) of water in the atmosphere and the mean distance traveled from evaporation sources to precipitation sinks. Meanwhile, geochemical tracers such as stable water isotope ratios provide a tool to probe hydrological processes, yet their interpretation remains equivocal despite several decades of use. As a result, there is a need for new mechanistic tools that link variations in water isotope ratios to underlying hydrological processes. Here we present a new suite of "process‐oriented tags, " which we use to explicitly trace hydrological processes within the isotopically enabled Community Atmosphere Model, version 6 (iCAM6). Using these tags, we test the hypotheses that precipitation isotope ratios respond to parcel rainout, variations in atmospheric RT, and preserve information regarding meteorological conditions during evaporation. We present results for a historical simulation from 1980 to 2004, forced with winds from the ERA5 reanalysis. We find strong evidence that precipitation isotope ratios record information about atmospheric rainout and meteorological conditions during evaporation, but little evidence that precipitation isotope ratios vary with water vapor RT. These new tracer methods will enable more robust linkages between observations of isotope ratios in the modern hydrologic cycle or proxies of past terrestrial environments and the environmental processes underlying these observations. Plain Language Summary: The heavy‐to‐light isotope ratio of atmospheric water, which records a wide array of water cycle processes, is readily observable and has therefore long been thought to hold much promise to help examine changes in water cycle processes. However, as multiple processes influence water isotope ratios, it is often difficult to tie observations to hydrological processes without using an atmospheric model. In this work, we develop a comprehensive set of numerical tracers to elucidate water cycle processes in the atmosphere from source to sink. In the context of water isotope ratios, these numerical tracers provide a method to explicitly test hypotheses of how variations in water isotope ratios map to underlying hydrological processes. The new tracers we outline here permit a fuller understanding of the hydrologic cycle and allow new ways to test model parameterizations and understand the processes governing hydrologic change. Key Points: Process‐based tracers in iCAM6 allow for expanded hypothesis testing of water cycle change and more informed use of water isotope ratios The degree of parcel rainout is a primary control on both δ 18 O and d‐excess, consistent with Rayleigh theory Water vapor residence time does not strongly influence precipitation δ 18 O, but evaporative conditions influence precipitation d‐excess